Effects of constituting material and interfacial crack on mechanical response of nanoscale metallic bilayers – a quasi-continuum study. Issue 15 (12th October 2020) - Wu, Cheng-Da; Fang, Te-Hua; Su, Wen-Cheng; Fan, Yu-Cheng
ABSTRACT: The effects of the constituting material and an interfacial crack on the deformation and mechanical response of metallic bilayer films under tension are studied using quasi-continuum simulations in terms of atomic trajectories, stress distribution and the stress–strain curve. The simulation results show that bilayer films with identical constituting monolayers have higher tensile strength than that of those with different monolayers. For bilayer films with different monolayers, the layer interface acts as a barrier that resists dislocation propagation. Dislocation emission at a crack tip blunts the tip. Necking originates at the layer interface and develops on monolayers with relatively low strength. A rectangular crack is less likely to develop than a V-shaped crack.